2021
DOI: 10.1002/ejp.1779
|View full text |Cite
|
Sign up to set email alerts
|

Patient reported outcome measures in trigeminal neuralgia – A systematic review of psychometric performance

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Another problem in evaluating the outcome after a surgical procedure for TN is the lack of consideration of the psychological aspects. A systematic review by Nova et al [ 40 ] stated that there was limited evidence of the psychometric performance of patient-reported outcomes for TN. Sandhu et al [ 41 ] reported on the minimum clinically important difference (MCID) interfering with activities of daily life (ADL) in facial pain using the Brief Pain Inventory Score (BPI).…”
Section: Discussionmentioning
confidence: 99%
“…Another problem in evaluating the outcome after a surgical procedure for TN is the lack of consideration of the psychological aspects. A systematic review by Nova et al [ 40 ] stated that there was limited evidence of the psychometric performance of patient-reported outcomes for TN. Sandhu et al [ 41 ] reported on the minimum clinically important difference (MCID) interfering with activities of daily life (ADL) in facial pain using the Brief Pain Inventory Score (BPI).…”
Section: Discussionmentioning
confidence: 99%
“…The study was divided into five stages—see Figure 1 for details. Consensus methods are described in the present paper (stages 3 and 4); stages 1 and 2 have been described separately (Venda Nova et al, 2020 ; Venda Nova et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…[3] TN patients have increased symptoms such as anxiety, depression, insomnia, affecting basic psychological, physical, social needs and activities of patients, and TN is even called suicide disease. [1,4] Microvascular decompression (MVD) is the first-line surgical therapy for medically refractory patients. Lars Bendtsen et al [3] reported that MVD had a good effect, and 62% to 89% of patients exhibited no pain at follow-up (3-11 years later), but Giorgio Cruccu hold different opinions, he reported about 50% of TN patients also have persistent pain in the same area in addition to the characteristic paroxysmal episodes.…”
Section: The Authors Have No Funding and Conflicts Of Interest To Dis...mentioning
confidence: 99%
“…Trigeminal neuralgia (TN) is a disturbing chronic pain condition on 1 side of the face. The International Classification of Headache Disorders and International Classification of Orofacial Pain defined TN as “a recurrent unilateral transient electroshock-like pain that has a sudden onset and termination, limited to the distribution of 1 or more divisions of the trigeminal nerve and triggered by harmless stimuli.” [1] Touching the face, talking, eating, or drinking can all cause fierce pain. The nature and severity of the pain maybe related to delayed diagnosis, fear of pain, side effects of medications, and lack of psychological support.…”
Section: Introductionmentioning
confidence: 99%